Pemuda dan Panggilan Kepemimpinan dalam Pelayanan Gereja (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
Amidst the current of globalization and rapid technological development, the role of youth in church ministry is increasingly receiving attention. Youth are not only seen as the next generation, but as an important part of the church community that has great potential in leading, innovating, and reaching the world contextually. This study aims to examine the calling of youth leadership in church ministry as a spiritual and social responsibility. Through a qualitative approach with a literature analysis method, this study examines the concept of servant leadership rooted in biblical values, as well as the importance of character building, spiritual growth, and providing space for youth to be actively involved. The results of the study indicate that the church needs to foster and entrust strategic roles to youth so that they are able to respond to the challenges of the times with humility and integrity. True leadership is based on the example of Christ who served, loved, and sacrificed. Therefore, the formation of young church leaders must be carried out holistically, sustainably, and contextually.